Endotelium Arteria Coronaria Tikus Putih Sprague Dawley Hiperlipidemia setelah diberi Chitosan Cangkang Udang Laut (Penaeus monodon F.) - Isdadiyanto, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
The objective of this study was to analyze the influence of chitosan on arteria coronaria endothelium of Sprague Dawley rats induced by high fat ration. The animals for this study were twenty adult male rats divided into four groups, i.e. group I as the control was fed with basal ration containing normal fat for 3 months, group II was fed ration containing high fat for 3 months, group III was fed ration containing high fat and given chitosan 180 mg per kg body weight per day orally in 2 ml aquadest for 3 months, group IV was fed ration containing high fat for 3 months and after 1 month given chitosan 180 mg per kg body weight per day orally in 2 ml aquadest for 2 months. Each group consisted of five animals. After 90 days, the rats were necropsied and the heart were collected to histopathological. CRP expression on coronary artery of rats that given normal diet were negative, whereas rats that given high fat diet and no treatment were positive. CRP expression of coronary artery for rats that given high fat diet and given chitosan were negative, but rats that given chitosan after one month were positive. Based on the result of this study, it was concluded that high fat ration was a major factor induced inflammation in coronary artery and chitosan was able to prevent disfunction of arteria coronaria endothelium cel. Â  Keywords: Atherosclerosis, arteria coronaria endothelium, chitosan, high fat ration.